Conceptualising and testing the relationship between actual and perceived motor performance: A cross-cultural comparison in children from Australia and Germany. Issue 17 (1st September 2020) - Tietjens, Maike; Barnett, Lisa M.; Dreiskämper, Dennis; Holfelder, Benjamin; Utesch, Till Onno; Lander, Natalie; Hinkley, Trina; Schott, Nadja
ABSTRACT: Previous studies investigating the relationship between motor skill, physical activity and fitness in children have not thoroughly considered the role of self-perception. Therefore, the study aim was to test a theoretical framework, which considered both actual and perceived motor skill as well as actual and perceived fitness. Potential moderating effects of sex and country were considered. Data on motor skill, fitness, as well as self-perception of motor skill and fitness were collected from 145 Australian children and 214 German children (age range 7 to 10 years). For actual motor skill and fitness, mean differences for sex, age and country were found. For perceived motor performance (perceived motor skill and perceived fitness) no mean differences were found for age. Path analyses were performed. The final model showed significant relations between actual performance (object control skill, fitness) and perceived performance (object control skill, fitness). All model paths had low to moderate regression weights with the lowest relationship reported between actual and perceived fitness. Sex and country showed no effects. This integrated approach has led to a better understanding of the relationship between children's perceived and objective performance, and cultural differences within them.